Probiotic, antimicrobial, antioxidant and sensory properties of fermented donkey milk with Lactobacillus fermentum ME-3 and Lactobacillus acidophilus (ATCC 4356) - Papademas, Photis; Parmaxi, I; Aspri, Maria (My University, 2015)
The aim of this study was to investigate the ability of the probiotic L.fermentum ME-3 and L.acidophilus (ATCC4356) to ferment pasteurized donkey’s milk, keeping it in cold storage for 14 days and testing end products for antimicrobial, antioxidant activities and sensory properties. Fermented donkey milks had pH values of 4.5 - 4.6 just after fermentation and they maintained high bacterial counts (8.5 log cfu ml-1) during cold storage for 14 days. The antimicrobial activity of L.fermentum ME-3 milk was highest against E.coli NCTC12241, while L.acidophjlus (ATCC4356) milk showed a greater zone of inhibition against Salmonella typhimurium NCTC120123. Lysozyme activity of raw, pasteurized and fermented milks remained high and values did not significantly differ. The antioxidant activity (FRAP) of fermented L. acidophilus (ATCC4356) was highest in Day 1 (65.4±4.7 μmol-1) when compared to L.fermentum ME-3 (46.0±5.1 μmol-1). L.fermentum ME-3 milk was assessed (p<0.05) as more refreshing, “light” and less viscous than L.acidophilus (ATCC4356) milk.
Keywords: Donkey milk; Fermentation; Lactic acid bacteria; Antimicrobial activity; Antioxidant activity